Travel Motivations and Perception of Tourists to Lower Subansiri District of Arunachal Pradesh, India (International Journal of Engineering and Computer Science, 2017)
The Lower Subansiri district is one of the oldest district of Arunachal Pradesh. The district is rich in natural as well as cultural aspects, which motivates the tourists to visit the district. Without motivation to travel, there would be no tourism industry. Although there are thousands of tourist destinations, the perspective of the tourist is usually confined by a number of factors. However, it was found that there was no proper research conducted on the travel motivation and perception of tourists visiting the Lower Subansiri district. The purpose of this study was to determine the motivating factors perception on entry formalities, tourism infrastructure and services etc., which plays an important role to encourage the tourism in the district.